Sphinctanthus hasslerianus and S. microphyllus (Rubiaceae): taxonomic identity, lectotypifications and conservation assessment and chorology - Salas, Roberto M.; Florentín, Javier E.; Nuñez Florentin, Mariela (Phytotaxa, 2022)
As part of a series of taxonomic and floristic studies of Rubiaceae from Southern Cone of South America, here we focus our attention on the genus Sphinctanthus. The genus has five species mostly distinguished by their hermaphrodite flowers, corollas with an internal moniliform ring of hairs, and pollen grains released in monads. In the study area, only Sphinctanthus hasslerianus was mentioned as native, however, most of the specimens are identified by the specialists either as S. microphyllus or S. hasslerianus. After a detailed study of all original available and numerous herbarium specimens, we formally treat S. hasslerianus is a new synonymous of the older name S. microphyllus. Additionally, lectotypes for both names are designated. The species is described, illustrated, all specimens studied are cited, and conservation status and comments on its geographic distribution are provided.